Use of Citrated Whole Blood for Point-of-Care Viscoelastic Coagulation Testing in Dogs - York, Whitney; Smith, M. Ryan; Liu, Chin-Chi (Frontiers in Veterinary Science, 2022)
A new portable bedside coagulation monitor (VCM Vet) has provided a user-friendly, cartridge-based method to perform viscoelastic testing. However, the use of native whole blood limits the time to analyze the sample to minutes. The objective of this study is to assess whether citrated whole blood can be utilized with the VCM Vet and whether the results are comparable to those of native whole blood. A secondary objective is to assess the viability of citrated whole blood results after up to four hours of resting. The study population consisted of 10 healthy mixed breed dogs. Whole blood samples were collected via jugular venipuncture. Blood was immediately transferred to the VCM test cartridge for native whole blood control groups per the manufacturer’s instructions, and the remainder was used to fill two 3.2% sodium citrate vacutainer tubes. Test group analysis was performed on samples from each tube concurrently after a rest period of 30 minutes (baseline), 2 hours, and 4 hours. Citrated whole blood samples were recalcified for analysis immediately prior to introduction into the cartridge. Data was recorded for all parameters. Results from the citrate groups were compared to the control group and to the citrated baseline to assess for differences. Overall results were compared using mixed ANOVA models. Where found, specific differences were evaluated using Tukey’s test. Within-sample variation was investigated and reported as median (range). A p < 0.05 was considered significant. Samples were obtained for 10 control and 20 citrated whole blood runs. Comparison of controls to citrated groups revealed significant differences in CT (p < 0.001) and MCF (p < 0.002). There were no significant differences between test groups compared to citrated baselines for any parameter. Selected median coefficients of variation were 6.8% (0-68.8%) for clot time, 2.4% (0-19.46%) for alpha angle, 3.2% (0-27.4%) for maximum clot firmness, and 0% (0-16.3%) for 45-minute lysis. Citrated whole blood samples can be used with the VCM Vet device; however, new reference intervals for use with citrated whole blood will be required. Results using citrated whole blood are not significantly different from baseline after up to 4 hours of resting.